Study on Clean Heating Technology and Engineering Case based on Computer Aided Implementation in North China. Issue 3 (October 2020) - Feng, Yanting; Chen, Haoyu; Lv, Yadong; Yan, Huibo; Yang, Chunlai; Feng, Xuyang
Abstract: Based on the concept of green and sustainable development, clean heating in northern China has become the key work of local governments, which has been gradually implemented in major cities to meet different heating supply. Therefore, in the new situation, we need to pay more attention to the high quality and sustainable heating mode. Under the new situation, clean heating in northern China needs to focus on optimizing the heating energy structure, which will improve the utilization rate of renewable energy. By strengthening the coordinated planning of the system, we can coordinate the available energy, which will build a multi energy complementary, green and efficient clean heating system. Based on Computer aided technology, we can realize the scheme design of clean heating system. Finally, this paper lists an engineering case.